Frequency of Hyperlipidemia among Patients of Hemorrhagic Stroke - Mumtaz, Tayyaba; Waheed, Sana; Javed, Muhammad Ali; Ali, Muhammad (Indus Journal of Bioscience Research, 2025)
Background: Increased risk for stroke is associated with hyperlipidemia for many years, particularly for ischemic stroke. However, its prevalence and association with hemorrhagic stroke are not so well known. It is important to establish the prevalence of hyperlipidemia among hemorrhagic stroke patients and its associations with clinical and demographic factors to aid stroke prevention. Objective: To determine the frequency of hyperlipidemia among patients of hemorrhagic stroke presenting at Ayub Teaching Hospital Abbottabad. Study Design: Cross-sectional study. Duration and Place of Study: The study was conducted from April 2024 to October 2024 at the Department of General Medicine, Ayub Teaching Hospital, Abbottabad. Methodology: A total of 95 patients aged 30–70 years with hemorrhagic stroke were enrolled. Hyperlipidemia was defined based on a serum cholesterol level ≥ 150 mg/dl. Data including age, gender, BMI, residential status, socioeconomic status, diabetes, and hypertension were recorded. Lipid profiles were obtained after an overnight fast. Results: The mean age of participants was 57.45 ± 8.15 years, with 68.4% male representation. Hyperlipidemia was found in 18.9% of patients. Significant associations were observed between hyperlipidemia and factors such as age (>50 years), male gender, rural residency, poor socioeconomic status, diabetes, and hypertension. Conclusion: This study highlights that while hyperlipidemia is more common in hemorrhagic stroke patients over 50 years of age.